2017
DOI: 10.3892/ijo.2017.3835
|View full text |Cite
|
Sign up to set email alerts
|

Combining doxorubicin with a phenolic extract from flaxseed oil: Evaluation of the effect on two breast cancer cell lines

Abstract: Breast cancer is one of the most frequently diagnosed forms of cancer and different treatments are used to block its progression. However, it still represents a very common cause of death in women. Doxorubicin (Dox) is reported as an effective agent in breast cancer treatment nonetheless it induces many side‑effects. For this reason, many laboratories are engaged in understanding how it is possible to decrease the drug concentration, considering that one of the possible solutions is to use drug synergy, combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…However, rapid treatment still leads to damaged heart tissue [17]. Other toxicities of DOX have been reported to be palmar-plantar erythrodysesthesia (also known as a hand-foot syndrome) [48] and typhlitis [57]. DOX's toxic impact on tissue is associated with:…”
Section: The Chronic Toxic Effect Of Doxorubicinmentioning
confidence: 99%
See 4 more Smart Citations
“…However, rapid treatment still leads to damaged heart tissue [17]. Other toxicities of DOX have been reported to be palmar-plantar erythrodysesthesia (also known as a hand-foot syndrome) [48] and typhlitis [57]. DOX's toxic impact on tissue is associated with:…”
Section: The Chronic Toxic Effect Of Doxorubicinmentioning
confidence: 99%
“…It is almost impossible to explain a single, unique apoptotic pathway induced by DOX [26]. However, literature data have suggested that DOX has been reported to trigger apoptosis in both pathways, intrinsic or mitochondrial and extrinsic [57,66].…”
Section: Apoptotic Cell Death Induced By Doxorubicinmentioning
confidence: 99%
See 3 more Smart Citations